The impact of corporate social responsibility on corporate tax aggressiveness —— adding executive age as a moderating variable - LUO, YUXIN (2022)
The frequent occurrence of corporate non-compliance with social responsibility and tax evasion in recent years has caused strong public discontent, making it critical to investigate the impact of CSR on tax-aggressive behaviour. Moreover, there is still a gap in research on the moderating effect of managerial age on the interaction between CSR and tax aggressiveness. The purpose of this paper is to investigate the relationship between corporate social responsibility and corporate tax aggressive behaviour, with executive age serving as a moderating variable. The relationship is analysed based on the three basic theories of corporate social responsibility, principal-agent theory, stakeholder theory, social contract theory and risk management theory. All listed companies on the Shanghai and Shenzhen A stock exchanges in China from 2015 to 2020 are used as the research sample. By constructing an empirical research model and using regression analysis to test the data, the study finds that corporate social responsibility is positively correlated with tax aggressiveness, but executive age is negatively correlated with tax aggressiveness, and this negative influence is more pronounced for SOEs. Furthermore, the reliability of the regression results is confirmed by endogeneity and robustness tests. The outcome of this research is useful for companies to understand the characteristics of management teams and the impact of CSR on tax planning, and provide tax authorities with new ideas on the factors that influence tax aggressiveness.